STRUGGLE FOR GENDER EQUALITY IN NIKI CARO'S NORTH COUNTRY: FEMINIST PERSPECTIVE - RAHMAWATI, FENY (2007)
The major problem of this study is to reveal how the struggle for gender equality reflected in Niki Caro's North Country. The objectives of the study are to analyze the film based on it's structural elements and on the feminist analysis. In analyzing the movie, the writer uses qualitative study. There are two kinds of data source. The primary data source is the movie of Niki Caro North Country, while the secondary data are books and internet websites related to the study. The method of collecting data source in the research is library research by watching the movie, summarizing, paraphrasing, and note-taking. The technique of data analysis is descriptive analysis. Having analyzed this movie, the writer draws conclusions as follows: first, literary work may reflect the social reality about women's struggle for gender equality. Second, Niki Caro want to say women and men are created equal.